An Alternative Mechanism for the Cobalt‐Catalyzed Isomerization of Terminal Alkenes to (Z)‐2‐Alkenes1. Issue 3 (27th November 2014) - Schmidt, Anastasia; Nödling, Alexander R.; Hilt, Gerhard
Abstract The cobalt‐catalyzed selective isomerization of terminal alkenes to the thermodynamically less‐stable (Z)‐2‐alkenes at ambient temperatures takes place by a new mechanism involving the transfer of a hydrogen atom from a Ph2PH ligand to the starting material and the formation of a phosphenium complex, which recycles the Ph2PH complex through a 1, 2‐H shift.